Control of ropes during the operation of machines with rope traction - Panfilov A.V.; Korotkiy A.A.; Ivanov B.F.; Yusupov A.R. (Научно-технический вестник Брянского государственного университета)
The methods of rope control during the operation of lifting structures, elevators, freight and passenger cable cars, funiculars and other machines with cable traction are considered. It is indicated that the main indicator of the technical condition of ropes is the appearance, development and interaction of defects that reduce the strength of ropes, contribute to their destruction and, accordingly, an emergency situation. The analysis of existing methods of rope control is carried out, the designs of flaw detectors are described, with the help of which the technical condition of ropes can be assessed during operation. It is established that one of the promising methods of control of steel ropes is optical based on machine vision and artificial intelligence technologies.